Na passarela da tradição: memórias e representações da formação docente no Colégio Dom Feliciano – Gravataí/RS (1970 – 1990) - Alexandrino, Artur Diego da Silva (Universidade do Vale do Rio dos Sinos, 2015)
This study investigates the production of a tradition of discourse on the College Dom Feliciano, located in the municipality of Gravataí / RS, through the narratives of teachers and students involved in the teacher education process between the years 1970 to 1990. This research aims to identify and analyze the elements underlying the schools tradition of discourse in the local community, and reflect on the process of teacher training and its relation to the production of this tradition. The research is based on the precepts of Cultural History and uses oral history as a methodology. The concept of tradition, prepared by Hobsbawn and Ranger, is paramount in the review process. Base dont his concept, it seeks to elements that assist in the identification and understanding of the tradition of discourse surrounding the school during the study period. Seeking to investigate the proposed objectives configure up two analytical categories: the identification and analysis of the elements that constitute and underlie the tradition of the school and teacher training. The reports of respondents, it appears that institutional tradition is consolidated in different elements. The tradition of the institution canbe perceived through the school building as a significant element of materiality and the influence of the invention of this tradition, as well as the motivations that led the se students to opt for professional training in this school. As for teacher training, discuss the narratives that help in perceptions and understandings of the characteristics that define the type of training conducted at the institution, which is characterized by the requirement of a vast production of teaching materials, in the subjectmatter as regulatory strategy and regulation, in religious precepts and speech quality of education. The teaching quality of speech is based, above all, discipline, training of teachers and the teaching practices that seek to reconcile the formal know led get ogether with educational teaching of an era.
Keywords: História das instituições; Formação de professores; Representação; Tradição e práticas pedagógicas; History of institutions; Teacher training; Representation; Tradition and teaching practices; ACCNPQ::Ciências Humanas::Educação